Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Di Klinik Spesialis Graha Amanah - Indratno, Okyawan Dwi; , Dr. dr. Iwan Setiawan Adji, Sp. THT-KL; , Drs. Wiyadi, M.M. Ph.D (2017)
The aim of this stduy is to identify and analyze the effect of: 1) the reliability of the patient's satisfaction. 2) The responsiveness patient's satisfaction. 3) The confidence (assurance) of patient's satisfaction. 4) The empathy of patient's satisfaction. 5) The tangible of patient's satisfaction. The data that used was primary data obtained from the answer of 100 respondents with the accidental method. The method that used was multiple linier regression analysis tool data using SPSS. The test result concluded that all variables instruments were valid and reliable as a tool of collecting the data. From the data analysis showed that: 1) The reliability has the positive and significant impact on patient's satisfaction. 2) The responsiveness has positive and significant impact on patient's satisfaction. 3) The confidence (assurance) has positive and significant impact on patient's satisfaction. 4) The empathy has positive and significant impact on patient's satisfaction. 5) And the tangible has positive and significant impact on patient's satisfaction.